KARAKTERISTIK KEWIRAUSAHAAN DAN PERUSAHAAN SERTA KOMPETENSI KEWIRAUSAHAAN SEBAGAI PENENTU KINERJA USAHA KECIL MENENGAH (UKM) - Hadiyati, Ernani (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
This project was intended to identify and analyze the simultaneous and partial influence of three observed variables, namely entrepreneurial characteristics, company characteristics, and entrepreneurial competencies, toward business performance. Further, this article explored the aspects contained in entrepreneurial characteristics, company characteristics, and competencies of entrepreneurs and small business performance which eventually resulted in the presentation of data regarding the relationship between the variables studied. The investigation demonstrated two important findings: first, entrepreneurial characteristics, firm characteristics, and entrepreneurial competencies had significant effect on the performance of small businesses simultaneously and partially; second, entrepreneurial competence was recognized as the most influential variables on the small businesses performance.